"Masculinities" in Sami studies - Olsen, Torjer A. (Journal of Northern Studies, 2016)
Sami masculinities must be understood as plural. This is the starting point for this article. There is little research done on gender and/in Sami society, especially concerning men and masculinity. The article deals with Sami masculinities as a field of research, and has two main goals. Firstly, the main trends in relevant research on gender in Sápmi in general and on Sami men in particular are presented and discussed. Secondly, a number of challenges related to doing research on Sami masculinities are explored. The theoretical perspectives are mainly drawn from the fields of gender studies and indigenous studies. The article will hopefully serve as a platform and a starting point for further research on Sami masculinities.